Implementation of Prudential Principles in Ba’i Bitsaman Ajil Financing and It Problem Mitigation in Baitul Maal Wattamwil - Heri Nugraha; Inne Risnaningsih; Siti Nurhayati; Resmi Sri Utami; Nurjamil Nurjamil2 (Indonesia Strategic Sustainability, 2021)
The research objective was to determine the Application of Prudential Principles in Ba'i Bitsaman Ajil Financing and its Problem Mitigation in Baitul Maal Wattamwil. Descriptive data using a qualitative approach. Collecting data collected through interviews, observation and documentation on the data at BMT Dana Ukhuwah. The results show that the application of the principle of prudence in the financing of Ba'i Bitsaman Ajil at BMT Dana Ukhuwah involves aspects of maximum funding limits and the principles of 5C and 1S in the guidelines for financing BMT Dana Ukhuwah practically only 3C (character, capacity, collateral). In addition, BMT Dana Ukhuwah asked Nomort to introduce a pension scheme to fix problematic financing as one of the triggers and increase Bai Bitsaman Ajil's support. The benefits of research for scientific progress and actual data on Islamic economics are related to the application of the precautionary principle to the funding of Ba'i Bitsaman Ajil, and serve as guidelines. Apart from being useful as information and input for further evaluation of the application of the precautionary principle in Ba'i Bitsaman Ajil funding so that it can be used as an assessment material by BMT Dana Ukhuwah and other cooperatives to mitigate probelamtic financing.